Social skills in interpersonal communication - Hargie, Owen.; Saunders, Christine; Dickson, David, 1930- (London : Routledge, 1994)
The subject of interpersonal skill has attracted research interest in recent years. This third edition of the text has been completely revised and rewritten to bring the book up to date. New chapters have been added on the social psychology of skilled communication.
Previous ed.: London : Croom Helm, 1987.
Keywords: Social skills; Interpersonal communication